Sea surface temperature datasets for climate applications from Phase 1 of the European Space Agency Climate Change Initiative (SST CCI). (17th September 2014) - Merchant, Christopher J.; Embury, Owen; Roberts‐Jones, Jonah; Fiedler, Emma; Bulgin, Claire E.; Corlett, Gary K.; Good, Simon; McLaren, Alison; Rayner, Nick; Morak‐Bozzo, Simone; Donlon, Craig
<x xml:space="preserve">Abstract</x> Sea surface temperature (SST) datasets have been generated from satellite observations for the period 1991–2010, intended for use in climate science applications. Attributes of the datasets specifically relevant to climate applications are: first, independence from in situ observations; second, effort to ensure homogeneity and stability through the time‐series; third, context‐specific uncertainty estimates attached to each SST value; and, fourth, provision of estimates of both skin SST (the fundamental measurement, relevant to air‐sea fluxes) and SST at standard depth and local time (partly model mediated, enabling comparison with historical in situ datasets). These attributes in part reflect requirements solicited from climate data users prior to and during the project. Datasets consisting of SSTs on satellite swaths are derived from the Along‐Track Scanning Radiometers (ATSRs) and Advanced Very High Resolution Radiometers (AVHRRs). These are then used as sole SST inputs to a daily, spatially complete, analysis SST product, with a latitude‐longitude resolution of 0.05°C and good discrimination of ocean surface thermal features. A product user guide is available, linking to reports describing the datasets' algorithmic basis, validation results, format, uncertainty information and experimental use in trial climate applications. Future versions of the datasets will span at least 1982–2015, better addressing the need in many climate applications for stable records of global SST that are at least 30 years in length.